35.0k views
1 vote
F(x)=4x+1 and g(x)=x^2-5 find f+g (x)

User JCVanHamme
by
4.5k points

1 Answer

3 votes

Answer & Step-by-step explanation:

When we see (f + g)(x), it means that we are adding together f(x) and g(x).

f(x) = 4x + 1

g(x) = x² - 5

(f + g)(x) = (4x + 1) + (x² - 5)

Combine like terms and make sure x² is in the front of the expression so you are following the rules of exponents when in standard form.

(f + g)(x) = x² + 4x - 4

So, (f + g)(x) equals x² + 4x - 4

User Brandon Howard
by
6.2k points